Board responsibility for irresponsibility: The link between board structure and corporate scandals - Gregor Dorfleitner; Christian Kreuzer (Schmalenbach Journal of Business Research (SBUR), 2024)
Based on an international data set that comprises over 6,100 companies located in 44 countries in the years 2002-2018, this paper analyzes the relation between corporate scandals and board structures besides further firm-related, political, nation-level economic, and cultural variables. We identify board structure variables that are positively associated with a~firm's corporate scandals, namely high CSR efforts and busy board members. There are also variables that are negatively associated with this kind of behavior, namely qualified and skilled boards. No clear evidence can be determined from a~board's gender diversity, independent board members, and board size.
Keywords: 650; Board structure; Corporate controversies; Corporate scandals; ESG controversies; Hybrid regression model; Within-between model